2017
DOI: 10.1039/c7ra08977e
|View full text |Cite
|
Sign up to set email alerts
|

A stable 3D Cd(ii) metal–organic framework for highly sensitive detection of Cu2+ions and nitroaromatic explosives

Abstract: A Cd(ii) coordination polymer, [Cd3(L)2(H2O)5]·(H2O)4(1) (H3L= 9-(4-carboxy-phenyl)-9H-carbazoly-3,6-dicarboxylic acid) has been synthesized solvothermally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 45 publications
(38 reference statements)
1
7
0
Order By: Relevance
“…The emission of HNU-50 shows a blue shift (31 nm) compared with that of PMA, which may be caused by the coordination of ligand to metal centers (Figure S6). Considering the Lewis acid-basic effect between the framework and U­(VI), the detection of U­(VI) by monitoring the fluorescence change of HNU-50 in solution was performed. As exhibited in Figure A, with the increase of U­(VI) concentration, the fluorescence of HNU-50 decreased gradually, and 70% of the fluorescence intensity was quenched at the concentration of 10 –3 M. Figure B shows the relationship of U­(VI) concentration and intensity (( I 0 – I )/ I 0 ), where I 0 is the measured luminous intensity of HNU-50 at 417 nm, and I is the fluorescence intensity of HNU-50 in solution with a given U­(VI) concentration at 417 nm.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The emission of HNU-50 shows a blue shift (31 nm) compared with that of PMA, which may be caused by the coordination of ligand to metal centers (Figure S6). Considering the Lewis acid-basic effect between the framework and U­(VI), the detection of U­(VI) by monitoring the fluorescence change of HNU-50 in solution was performed. As exhibited in Figure A, with the increase of U­(VI) concentration, the fluorescence of HNU-50 decreased gradually, and 70% of the fluorescence intensity was quenched at the concentration of 10 –3 M. Figure B shows the relationship of U­(VI) concentration and intensity (( I 0 – I )/ I 0 ), where I 0 is the measured luminous intensity of HNU-50 at 417 nm, and I is the fluorescence intensity of HNU-50 in solution with a given U­(VI) concentration at 417 nm.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Degradation of MB was also studied. In the presence of [126]. The free ligand showed emission at ~420 nm upon excitation at 356 nm.…”
Section: Carbazole Derivativesmentioning
confidence: 99%
“…Du et al [138] reported a 3D Cd(II) MOFs, constructed abundant carboxylate groups which can bind the metal ions by coordination. Cu 2+ could quench the fluorescent in water, and the color of MOFs was transformed from yellow to green by visual inspection, which improved the accuracy of the test results.…”
Section: Heavy Metal Detectionmentioning
confidence: 99%